2016
DOI: 10.1590/1807-1929/agriambi.v20n11p1008-1013
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of Tithonia diversifolia and attributes of the soil fertilized with biofertilizer in irrigated system

Abstract: The fertilization with biofertilizer associated with the use of irrigation favors nutrient uptake by plants and soil chemical properties; however, these effects are little studied in Tithonia diversifolia in semiarid regions. This study evaluated the effect of doses of bovine biofertilizer and irrigation on accumulation of nutrients in the leaves of Tithonia diversifolia plants and on soil chemical attributes. The study was carried out from December 3, 2014 to November 28, 2015, and arranged in a 2 x 5 factori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
3
0
10
Order By: Relevance
“…A maior disponibilidade de N, no solo do tratamento com ureia + NBPT, também pode ter ocasionado aumento da taxa de decomposição da MOS, diminuindo o pH do solo. A maior presença de N no solo promove a atividade microbiana responsável pela decomposição da MOS que pode aumentar a concentração de ácido carbônico (CO 2 + H 2 O H 2 CO 3 ), que se dissocia (H 2 CO 3 HCO 3 + H + ) e libera íons H + , reduzindo o pH do solo (Reis et al, 2016).…”
Section: Resultsunclassified
“…A maior disponibilidade de N, no solo do tratamento com ureia + NBPT, também pode ter ocasionado aumento da taxa de decomposição da MOS, diminuindo o pH do solo. A maior presença de N no solo promove a atividade microbiana responsável pela decomposição da MOS que pode aumentar a concentração de ácido carbônico (CO 2 + H 2 O H 2 CO 3 ), que se dissocia (H 2 CO 3 HCO 3 + H + ) e libera íons H + , reduzindo o pH do solo (Reis et al, 2016).…”
Section: Resultsunclassified
“…Los datos encontrados en proteína son consistentes con los reportados en la literatura a los 30 días de rebrote, donde se obtuvieron porcentajes entre 28.5 y 29.8 % (5,22) , y superiores a los reportados por otros autores, dado por los días al corte, altura de la planta al corte y fertilización (23,24,25) . La aplicación de biofertilizantes y riego incrementa significativamente la acumulación de nutrientes (26) .…”
unclassified
“…In the second date, it was observed that the highest pH value was obtained with the addition of 3 g of urea and the lowest pH (4.9) with the highest dose of urea (20 g). In the present work, the lowest values of pH with the use of highest urea dose can be explained by the fact that the higher presence of N in the soil increases the carbonic acid concentration, due to the greater microbial activity, which are dissociated and release H+ ions, reducing soil pH as in [18,19], promoting higher concentrations of acids, and consequently more acidic pH. What was also observed by Silva et al [20] when evaluating urea doses in 'Vitória' pineapple plant, and was verified a similar effect on soil pH with doses increased.…”
Section: Resultsmentioning
confidence: 62%